Removing the barriers in manufacturing: The 1990 European manufacturing futures survey - DE MEYER, Arnoud Cyriel Leo (Institutional Knowledge at Singapore Management University, 1991)
The 1990 European Manufacturing Futures survey shows that European manufacturers are doing well. Efforts in total quality management and improvement of deliveries are paying off; the factories have been cleaned up and reorganized. The creation of the post-1992 single market is not expected to change the total number of their factories, but is likely to demand a more customized output and service to more markets from each factory. More non-EC competitors are expected to enter and set up plants in Europe. The leading European manufacturers are focusing increasingly on establishing closer links between production and the other functions in the company as well as with suppliers, customers, and others outside the company. This is done partly through technology, partly through interfunctional teams, and partly by modification of procedures. The goal is to remove the barriers to free flow of information, goods and people to and from the factory. This is a bold move, but as the logical next step to the improvement efforts within the factory, it is unavoidable. The excitement of the 1992 single market, and the opening of the Eastern European markets, can hinder such risk-taking ventures in manufacturing. But, in fact because of the new opportunities, uncertainties and potential turbulence in Europe in the next few years, there is even more reason for bringing the factory in closer contact with its environment. This will be risky, but for the European manufacturers, the favorable recent results provide a window of opportunity to prepare for the factory without borders.